Research on Configurations for Marketing Performance of Science and Technology Enterprises in China Based on the TOE Framework - Jianing Zhang; Jianhong Fan; Xianghong Yan (SAGE Open)
Facing a complex and changeable business environment, enterprises are constantly looking for specific paths to improve their marketing performance, which may ultimately lead to a sustainable competitive advantage. Based on the Technology, Organization, and Environment (TOE) framework, this study uses a sample of 258 listed science and technology enterprises in China and applies the Fuzzy Set Qualitative Comparative Analysis (fsQCA) method to examine the relationship between six conditions, namely, R&D capability, information technology application capability, marketing level, enterprise scale, government support, market competition, and marketing performance of science and technology enterprises from a configurational perspective. The results show that no single condition qualifies as necessary for high marketing performance, but the role of high enterprise scale is prominent. Four paths generate high marketing performance of science and technology enterprises and four paths generate not-high marketing performance. These paths have an asymmetric causal relationship between high and not-high marketing performance. This study provides a new perspective for research on enterprise marketing performance and implications for enhancing the marketing performance of science and technology enterprises.